2015
DOI: 10.1103/physreve.92.012109
|View full text |Cite
|
Sign up to set email alerts
|

A+Amodel with a bias towards nearest neighbor

Abstract: We have studied the A+A→∅ reaction-diffusion model on a ring, with a bias ε(0≤ε≤0.5) of the random walkers A to hop towards their nearest neighbor. Though the bias is local in space and time, we show that it alters the universality class of the problem. The z exponent, which describes the growth of average spacings between the walkers with time, changes from the value 2 at ε=0 to the mean-field value of unity for any nonzero ε. We study the problem analytically using independent interval approximation and comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The asymptotic behavior of the density ρ of the AWLA was first reported in Ref. [30] for σ = 0 and later in Ref. [33] for any σ, which is…”
Section: Modelmentioning
confidence: 63%
See 2 more Smart Citations
“…The asymptotic behavior of the density ρ of the AWLA was first reported in Ref. [30] for σ = 0 and later in Ref. [33] for any σ, which is…”
Section: Modelmentioning
confidence: 63%
“…Recently, another form of bias that cannot be removed by the Galilean transformation was introduced [30], initially motivated from opinion dynamics [31,32]. This hopping bias is implemented in such a way that a particle prefers hopping toward its nearest particle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (S1.1) reduces to standard equations in the literature [1] when 32 describing with two competing strains. Unfortunately, equation (S1.1) becomes analytically 33 intractable when multiple strains and selective advantages are present because of the closure Neutral correlation functions 37 Much is known about equation (S1.1) in the neutral case where all s i = 0 as discussed in the main 38 text [1]. Unsurprisingly, it can be shown that the average fraction F i = f i equals the initial…”
mentioning
confidence: 99%
“…To control for this fact, we grew the colonies used to 29 determine u i and u j on the same plate as the colony used for evaluating v ij w directly from the 30 motion of domain walls, i.e., on one plate we inoculated a colony of a fast growing strain i, a 31 colony of a slower growing strain j, and a mixed colony composed of 10% of strain i and 90% of 32 strain j. The mixed colony's ratio of strains was chosen so that single sectors of the more fit 33 strain would form. 34 Using the radial expansion velocities of the i and j expansions (u i and u j ) in eq.…”
mentioning
confidence: 99%